Exploring the interplay between Fusobacterium nucleatum with the expression of microRNA, and inflammatory mediators in colorectal cancer - Bostanghadiri, Narjess; Razavi, Shabnam; Shariati, Aref; Talebi, Malihe; Mirkalantari, Shiva; Emami Razavi, Amirnader; Darban-Sarokhalil, Davood (Frontiers in Microbiology, 2023)
Background: Fusobacterium nucleatum has been recognized as an important key bacterium in the cause and spread of colorectal carcinogenesis. Nevertheless, the clinical relevance of F. nucleatum in colorectal cancer (CRC) and its effect on immune factors and the tumor microenvironment have not been fully elucidated. Materials and methods: The frequency of F. nucleatum was measured in 100 paired tumor and normal tissue specimens by TaqMan quantification Real-Time Polymerase Chain Reaction (qPCR). The mRNA expression levels of cytokines (IL-6, IL-10, IL-12β, IL-17, TNF-α, TLR-2, and TLR-4), and miRNAs (miR-21, miR-31) were examined. Eventually, any potential correlations between the molecular and clinicopathological features of the neoplastic samples and the abundance of F. nucleatum were analyzed. Results: The relative frequency of F. nucleatum was significantly increased in cancerous tissue compared to adjacent non-tumor tissues. Furthermore, the high level of F. nucleatum was significantly associated with histological grade III and IV CRC tissues (P=0.027 and P=0.022, respectively) and perineural invasion-positive patients (P=0.037). In addition, the expression levels of IL-6, IL-17, TNF-α,IL-12β, TLR-2, and TLR-4 as well as miR-21 and miR-31 showed a significant increase in the cancer group. A notable correlation was also observed between the high status of F. nucleatum and the expression of IL-6, TNF-α and miR-21. Conclusion: Our results emphasize the importance of F. nucleatum and changes in the expression of genes involved in CRC. Studying the microbial profile and gene expression changes in CRC patients may be a promising approach to improve screening methods and provide therapeutic strategies.